Sentiment Analysis of Platform X Users on Starlink Using Naive Bayes - M. Khalil Gibran; Rifki, Mhd Ikhsan; Hasugian, Abdul Halim; Siahaan, Ahmad Taufik Al Afkari; Afandi Sahputra; Ong, Russell (Cattleya Darmaya Fortuna, 2024)
This research aims to analyze public sentiment towards Starlink through tweets collected using the hashtag